PERFORMANCE OF THE ACTIVE SIAGA VILAGES AT THE AREA SUKODONO COMMUNITY HEALTH CENTRE - Noviana, Ayu Cahyani (Universitas Wijaya Kusuma Surabaya, 2014)
In relation to be built âHealthy Districtâ. Sukodono Community Health Centre wanted to evaluate all of the Siaga Villages performance at the area and tried to be upgraded the rank , if possible to be at the best rank. The result showed that at 2013 there was no more first grade Siaga Villages, 52.63% became second grade and 10,53% became third grade but the highest grade was none. To achived the highest grade was very difficult due to limited human resources at the village, so Sukodono Community Health Centre has to do some workshops and gives some rewards to the villagers to attrack them to become the participants